PENGARUH E-COMMERCE (STUDI KASUS PADA APLIKASI SHOPEE) TERHADAP MINAT BELI PAKAIAN PRIA DEWASA PADA MAHASISWA PRODI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PALEMBANG - Muhammad Lisdan Pondarta; Nenny Octarinie; Rusma Rizal (TECHNOBIZ : International Journal of Business, 2025)
Digital marketing is present as a new innovation in the world of marketing. Digital marketing is the process of marketing a product or service via digital means or the internet. Nowadays, people can choose to make purchases online or conventionally. Marketing via the internet allows customers to choose the product or service they want without having to waste time going to the place where they need the product or service. The aim of this research is to examine the influence of e-commerce on interest in purchasing adult clothing among students at the economics faculty at Palembang University. The sample in this research was male students from the Management Studies program, Faculty of Economics, Palembang University. The research method is presented quantitatively, based on questionnaires distributed to respondents. Next, the data was processed using the SPSS 26 program. The final aim of this research is to find out whether all the indicators in the e-commerce variable have an effect on the purchase interest variable.